Strategi Pengembangan Good Agricultural Practices (GAP) di Kabupaten Bangka, Provinsi Kepulauan Bangka Belitung - Fournita Agustina; Imron Zahri; Muhammad Yazid; . Yunita (Jurnal Ilmu Pertanian Indonesia, 2017)
The purpose of this study is to identify the problems faced by agricultural extension workers and to formulate alternative of extension strategies in realizing the application of horticultural GAP by farmers in Bangka Regency. This study was conducted in Bangka Regency of Bangka Belitung Province in February 2014. The data obtained in the field were analyzed using qualitative descriptive analysis and SWOT analysis method. The results of this study indicate that: (1) The problems faced by agricultural extension workers in realizing the application of horticultural GAP by farmers in Kabupaten Bangka are low knowledge and skill about GAP horticulture, the existence of agricultural extension workers that have heavy work load, programme extension does not correspond to the need of farmer horticulture; (2) The strategy of agricultural extension workers in realizing the application of GAP horticulture by farmers in Bangka Regency is to increase the training and visit and demonstration plot (plots) GAP horticulture, applying to the Food Security Agency of Bangka Regency related to the lack of education and learning tools horticulture, increasing knowledge and skills on horticultural GAP. Enhance interaction with universities and research institutions, knowledge and skills based on experience farming horticultural crops farmers as well as keeping exercise routines and visits to horticultural farmers